Trinidad - (:unkn) unknown (My University, 2009)
The giant Samaan tree provides cover for the automoblies parked in front of the Trinidad Country Club.
Colour; Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Clubs--Trinidad and Tobago; Trees--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Trinidad Country Club